Evaluasi Kondisi Jalan Angkut dari Front Penambangan Menuju Rom Stockpile untuk Mencapai Target Produksi 15.000 Ton Batubara Perbulan PT. Prima Dito Nusantara Jobsite KBB Kabupaten Sarolangun, Provinsi Jambi - Bram Subhan Maulana; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
Coal production produced by PT. Prima Dito Nusantara by dumptruck is currently 9.977,48 ton/bulan, looking at the condition of the existing equipment, it is planned to produce daily from the dumptruck to be further improved so that the production that can be achieved by the dumpt truck can reach 15,000 tons / month. Therefore, the problem to be examined is